(untitled) (Research, Society and Development, 2018)
The study aims to systematically review the scientific literature about the process of teacher training for the teachers, considering that many bachelors in Administration works in the Teaching area, some of them without mastery of pedagogical skills and abilities. The review was done in the Instituto Brasileiro de Informação em Ciência e Tecnologia, in the Thesis and Dissertation bank of the Coordenação de Aperfeiçoamento de Pessoal (CAPES), in the WebQualis Platform and in the CAPES periodicals portal. The search interval was from 2010 to 2016 and we selected 33 studies. The results indicate the possible omission in the administrator pedagogical training and also the lack of continuous training policies to improve their teaching practices. Thus, it is considered that, the teacher training is of extreme importance for the development and constitution of the Administration’s teacher and, it is evident the appreciation by the teachers by a continuous pedagogical training that presents as an alternative for the improvement of the teaching practice in the Administration’s courses.